2019
DOI: 10.5713/ajas.18.0504
|View full text |Cite
|
Sign up to set email alerts
|

White striping degree assessment using computer vision system and consumer acceptance test

Abstract: Objective The objective of this study was to evaluate three different degrees of white striping (WS) addressing their automatic assessment and customer acceptance. The WS classification was performed based on a computer vision system (CVS), exploring different machine learning (ML) algorithms and the most important image features. Moreover, it was verified by consumer acceptance and purchase intent. Methods The samples for image analysis were classified by trained speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…The use of photos had already been proven as an effective method for the visual evaluation of raw chicken breasts, so the procedure was used during the white striping evaluation. ( WS ) (Kato et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of photos had already been proven as an effective method for the visual evaluation of raw chicken breasts, so the procedure was used during the white striping evaluation. ( WS ) (Kato et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Color alterations, as the presence of pale and yellowish regions, and protuberances on the surface (Sihvo et al 2014 ), may influence directly consumer´s acceptance and purchase intention. Kato et al ( 2019 ) investigated the perception of American and Brazilian consumers, respectively, in relation to the appearance of chicken fillets with white striping ( WS ), an anomaly that may occur simultaneously with WB . Both studies used photographic images during the evaluation and found out that, as the anomaly degree of severity increases, acceptance and purchasing intention decreases significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Besides texture, color is a very important meat trait that drives consumer choice, especially for raw meat, as consumers want to see the product [2]. Nevertheless, less attention has been given to this quality trait in relation with texture when myopathies occur focusing more in appearance and firmness aspects [13] more related to texture. Different texture devices and tests have been used assessing major pectoralis myopathies, such as Meullenet-Owens razor shear [14,15], Allo-Kramer shear [16], Warner-Bratzler shear [17] or texture profile analysis (TPA) which is more commonly used in this species [14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…(2014) showed that reduced growth rate results in lower occurrence and severity of WS in broiler breast muscle, which also supported the hypothesis that higher metabolic rate plays a vital role in the occurrence of WS. Different studies have shown that WS had negative impacts on overall breast meat quality by worsening WHC and tenderness ( Bowker and Zhuang, 2016 ; Brambila et al., 2016 ; Kato et al., 2019 ). On the other hand, Mudalal et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2015) reported that WS had a negligible or relatively low effect on meat quality. Besides reducing meat quality, the appearance of WS was shown to affect consumer acceptance negatively ( Fletcher, 2002 ; Kato et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%